Enhancement of Fish Immunity and Survival Rate Through Dietary Supplementation with Sargassum sp. Powder - Sri Wahyuni; Asri Mursawal; Anisa Mardhatila; Ronal Kurniawan; Ervia Yudiati (Jurnal Perikanan dan Kelautan, 2026)
Pathogenic bacterial infections in intensive aquaculture systems are among the primary causes of high fish mortality, underscoring the need for safe, sustainable natural antibacterial alternatives. Sargassum sp. is known to contain bioactive compounds with potential antibacterial and immunostimulatory properties. This study aimed to evaluate the effects of dietary supplementation with Sargassum sp. powder on the immune response and survival rate of Nile tilapia (Oreochromis niloticus). The experiment was conducted using a Completely Randomized Design (CRD) with one factor and five treatments: negative control (Kn), positive control (Kp), and dietary treatments P1 (15 g/kg feed), P2 (30 g/kg feed), and P3 (45 g/kg feed). Observed parameters included hematological profiles (erythrocytes, leukocytes, hemoglobin, hematocrit, and leukocrit) and survival rate during 30 days of rearing. The results showed that dietary supplementation with Sargassum sp. powder significantly improved hematological parameters in Nile tilapia compared with the control groups. The highest values were observed in P1, with total erythrocytes (1.66 × 10⁶ cells/mm³), hemoglobin (8.73%), hematocrit (31.3%), and leukocrit (1.67%). The highest survival rate was also recorded in P1 and Kp (100%). Therefore, the inclusion of Sargassum sp. powder at 15–30 g/kg feed is recommended as the optimal dosage to enhance the immunity and survival rate of Nile tilapia